Paying for Green: Environmental Awareness and Price Premium Among Young Indonesian Consumers - jayadi, Jayadi; Herman, Andi Anna (Journal of Business Administration (JBA), 2026)
This study examines the influence of Environmental Awareness (EA) on Perceived Price Premium (PPP) toward environmentally friendly packaging of Pop Mie among young Indonesian consumers aged 17–23. While green product attributes are often associated with consumers’ willingness to pay higher prices, this study investigates whether greater environmental awareness leads to stronger acceptance of price premiums in a low-cost fast-moving consumer goods (FMCG) category. Using a quantitative approach, data were collected from 100 students of Politeknik Negeri Ujung Pandang who had consumed Pop Mie. Respondents were selected through accidental sampling. Simple linear regression was employed to test the relationship between EA and PPP, supported by normality, heteroskedasticity, and linearity tests. The results indicate a statistically significant negative relationship between EA and PPP (β = –0.248, p = 0.042), suggesting that consumers with higher environmental awareness are less likely to perceive premium pricing as justified. This finding implies that pro-environmental attitudes do not necessarily translate into greater willingness to pay, particularly when sustainability claims are not supported by clear benefits or value. The model explains only 4.2% of the variance in PPP (R² = 0.042), indicating that other factors, such as brand image, perceived quality, and functional value, may have a stronger influence on price perceptions. These findings challenge the assumption that environmental concern consistently increases acceptance of green price premiums. The study contributes to the green consumer behavior literature by highlighting the importance of economic considerations in emerging markets and provides practical insights for marketers seeking to balance sustainability initiatives with consumer affordability expectations.